VALIDATION OF MARKER-TRAIT ASSOCIATIONS IN SIX-ROWED BARLEY LINES BRED IN KAZAKHSTAN - Amalova, A.; Genievskaya, Yu.; Abugalieva, S.; Chudinov, V.; Turuspekov, Ye. (Eurasian Journal of Applied Biotechnology, 2022)
Barley is an important cereal crop in Kazakhstan, mostly used for animal feeding, malting, and the food industry. The success of barley production is dependent on the genetic resources (cultivars) available, and local breeding programs that focus on the development of competitive cultivars. One way to develop new high-yielding cultivars and improve the efficiency of breeding programs is the application of modern molecular genetic and genomic tools. One such technology is genome-wide association study (GWAS), which has been successfully applied to identify the quantitative trait loci (QTL) associated with the valuable traits. The identified single nucleotide polymorphisms (SNPs) based on GWAS can be converted to flexible and cost-effective KASP (Kompetitive Allele Specific PCR) assays and validated for use in future marker-assisted breeding projects. The purpose of this study was to genotype eleven promising six-rowed barley lines using twenty-one KASP assays associated with agronomic traits reported in previous GWAS. The genotyping results suggested that only seven out of twenty-one KASP markers were polymorphic in this group of barley accessions. The t-test output suggested that six out of nine agronomic traits were significantly associated with seven KASPs. Notably, two assays (ipbb_hv_6, ipbb_hv_108) affected both vegetation period (VP) and yield per m2 (YM2) in conditions of Northern Kazakhstan, where barley is growing in more than 80% of total crop sowing areas of the country. The application of these highly informative KASP markers can help enhance the efficiency of local breeding projects in barley.